2019
DOI: 10.1590/1981-6723.25318
|View full text |Cite
|
Sign up to set email alerts
|

Turnip (Brassica Rapus L.): a natural health tonic

Abstract: In addition to basic nutrition, plant-based foods provide substantial amounts of bioactive compounds which deliver desirable health benefits. During the last decade, secondary metabolites, also known as phytochemicals, obtained from plants, have aroused special attention by researchers. Amongst such plants, the turnip contains a few valuable components which not only endorse health benefits but also provide healing properties. Various bioactive components, for example peroxidase, kaempferol, phenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Likewise, it is difficult to properly classify phytochemical because have differences in the origin, stage of development and composition of each Brassica group (Gómez-Gómez & Boller, 2000). In general, the phytochemicals as secondary metabolites (terpenoid, alkaloids, phenolic compounds, lignins, plants steroid, curcumines, saponins, flavonoids, glucosides), depending on their role in plant metabolism (Ferreira, Passos, Cardoso, Wessel, & Coimbra, 2018) are synthesized as defense system (Javed et al, 2019). In particular, the Brassica is rich in phytochemical compounds recognized as bioactive secondary metabolites naturally occur in these plants, have the capacity to act on diverse molecular targets into the cells.…”
Section: Main B I Oac Tive Phy To Chemi C Al S In B R a Ssic A Pl Antsmentioning
confidence: 99%
“…Likewise, it is difficult to properly classify phytochemical because have differences in the origin, stage of development and composition of each Brassica group (Gómez-Gómez & Boller, 2000). In general, the phytochemicals as secondary metabolites (terpenoid, alkaloids, phenolic compounds, lignins, plants steroid, curcumines, saponins, flavonoids, glucosides), depending on their role in plant metabolism (Ferreira, Passos, Cardoso, Wessel, & Coimbra, 2018) are synthesized as defense system (Javed et al, 2019). In particular, the Brassica is rich in phytochemical compounds recognized as bioactive secondary metabolites naturally occur in these plants, have the capacity to act on diverse molecular targets into the cells.…”
Section: Main B I Oac Tive Phy To Chemi C Al S In B R a Ssic A Pl Antsmentioning
confidence: 99%
“…Turnip leaves possess more nutrients compared with turnip roots. Besides the nutrients mentioned above, some researchers reported that turnip leaves are abundant sources of carotenoids, lutein, vitamin A, vitamin B, and vitamin K ( 22 ).…”
Section: Chemical Composition Of Turnipmentioning
confidence: 99%
“…Both the roots and leaves have a pungent flavor and the edible portions of the turnip are used as an ingredient in stews and soups. Similarly, turnip tops and turnip greens have been used as vegetable products in some parts of the globe (Schonhof et al, 2007 andJaved et al, 2019).…”
Section: Introductionmentioning
confidence: 99%